ISO 31000's Role in Strengthening Corporate Financial Resilience During COVID-19 Crisis - Indri Septiani; Yudhi Adhitya; Edy Jumady; Marwah Yusuf (IECON: International Economics and Business Conference, 2025)
The COVID-19 pandemic has posed severe financial threats to companies across sectors, exposing weaknesses in traditional risk response systems. To address the increasing uncertainty and the need for rapid strategic adjustment, this study evaluates the role of the ISO 31000 risk management framework in enhancing corporate financial resilience during crises. The research aims to assess how the implementation of ISO 31000—including risk identification, analysis, evaluation, and mitigation—affects key indicators of financial stability: liquidity, solvency, operational continuity, and strategic financial adaptation. A mixed-method approach was employed, combining qualitative descriptive analysis and quantitative correlational analysis using Likert-scale questionnaire data. Regression analysis, t-tests, and F-tests were used to examine the influence of each risk management component, supported by reliability testing via Cronbach’s Alpha. The results show that the four ISO 31000 components jointly have a significant influence on all dimensions of financial resilience. Among them, risk mitigation shows the most consistent and significant effect, indicating its critical role in stabilizing companies during turbulent conditions. In contrast, risk analysis has the least statistical impact across the models. This study contributes empirical evidence supporting the strategic application of international risk management standards during global crises. The findings offer practical implications for organizations seeking to institutionalize structured risk governance and reinforce financial resilience. It also expands the academic discourse on risk-based financial management and encourages further exploration of adaptive frameworks in times of high uncertainty.